Formulation And Testing Of Flavonoid And Vitamin C Levels Of Clay Mask Of Chinese Bidara Leaf Extract (Ziziphus Mauritiana Lam) For Aging Skin Care - Hannum, Lili Faridah; Minerva, Prima (Jurnal EduHealth, 2024)
Aging is a gradual process of tissue disappearance to repair or replace itself and maintain its normal structure and function. The aging process is caused by exposure to UV rays, daily habits, and improper facial skin care. In addressing aging, a good treatment is the use of clay masks. Facial skin aging can be treated by utilizing natural ingredients, one of which is Chinese date leaves (Ziziphus mauritiana Lam). Chinese date leaves contain anti-inflammatory and antioxidant properties as well as phytochemical compounds such as flavonoids and vitamin C. Clay mask formulations were designed by varying the concentration of Chinese date leaf extract, namely F0 (0%), F1 (2.5%), F2 (5%), and F3 (7.5%), with the aim of determining the best clay mask formulation. The Chinese date leaf extract was tested for flavonoid content using the UV-Vis spectrophotometer method and for vitamin C content using the titration method. The clay mask preparations were examined for organoleptic properties, pH, homogeneity, adhesive power, drying time, and hedonic test. The research results showed that Chinese date leaf extract had a flavonoid content of 1.5% and a vitamin C content of 82.6%. The results of the clay mask preparation met the requirements for organoleptic properties, pH, homogeneity, adhesive power, and drying time. Based on the results of various extract concentrations, satisfactory results were obtained, with formulations F1 and F2 meeting the requirements.